Rotavirus-Induced Neonatal Epileptic Encephalopathy—A Disease Spectrum Illustrated by Monochorionic Twins - Hopmans, Esther M.; van der Heide, Astrid; Chung, Pui Khi; Brinkman, Daniëlle; Feltkamp, Mariet C.W.; van Dijk, J. Gert; Steggerda, Sylke J.; Niks, Erik H. (Neuropediatrics, 2020)
Rotavirus has been associated with neonatal seizures and specific white matter magnetic resonance imaging (MRI) abnormalities. We describe monochorionic twins who not only tested positive for rotavirus with these white matter MRI abnormalities but who also showed an electroencephalogram (EEG) pattern characteristic of early infantile epileptic encephalopathy (EIEE), which has so far solely been described in epileptic encephalopathies with a poor prognosis. This report suggests that rotavirus infection must be added to the list of causes of EIEE EEG, and that the outcome then is likely more favorable. As MRI and EEG signs of rotavirus encephalopathy were present in one twin with only subtle neurologic symptoms, rotavirus may well cause insidious central nervous system complications more often. We suggest considering rotavirus infection in neonates presenting with seizures, and to add rotavirus infection to the differential diagnosis of EIEE.
Keywords: neonatal seizures; rotavirus; epileptic encephalopathy; EIEE; MRI